Using Modified Fly Ash for Removal of Heavy Metal Ions from Aqueous Solution - Thuy Chinh Nguyen; Trang Do Mai Tran; Van Bay Dao; Quoc-Trung Vu; Trinh Duy Nguyen; Hoang Thai (Journal of Chemistry)
This paper presents the characteristics of fly ash which was modified by 2-mercaptobenzothiazole (MBT) and sodium dodecyl sulfate (SDS) as the surfactants after treating with 1M NaOH solution. The change in morphology, specific surface area, crystal structure, and composition of the unmodified and modified fly ash was evaluated by FTIR, XRD, FESEM, BET, and EDX methods and techniques. The FTIR spectra of modified fly ash showed that there was no chemical reaction between the surfactants and fly ash. The XRD patterns and FESEM images indicated that modified fly ash had zeolite structure with a pore size of about 50 nm. Heavy metal ion adsorption behavior as well as adsorption isotherm models (Langmuir and Freundlich) of Cd2+ and Hg2+ ions of the unmodified and modified fly ash were also investigated and discussed. The amount of adsorbed ions of the modified fly ash was higher than that of the unmodified fly ash. The calculated results from the adsorption data according to the adsorption isotherm models of the above ions displayed that the Langmuir isotherm model was complied for the Cd2+ adsorption process while the Freundlich isotherm model was fitted for the Hg2+ adsorption process.